The People's Republic of China's Potential Growth Rate: The Long-Run Constraints - Jesus Felipe; Matteo Lanzafame; Juzhong Zhuang (Asian Development Bank (ADB), 2014)
We estimate the People's Republic of China's (PRC's potential growth rate in 2012 at 8.7% and at 9.2% for the average of 2008-2012, about the same as the average actual growth rate for this period. This rate is the natural growth rate, that is, the rate consistent with a constant unemployment rate and stable inflation. The PRC's natural growth rate displays a downward trend since 2006, when it peaked at 11.1%. Probably the Great Recession has been an important factor, although we argue that there are other factors. We show that the PRC's potential growth rate is not demand constrained, in particular by the balance of payments. The PRC's potential growth rate is determined by the supply side of the economy, in particular by: (i) changes in the structure of the economy, in particular in the share of industrial employment; (ii) the working-age population; (iii) the share of net exports in gross domestic product (GDP); (iv) export growth; (v) the share of foreign direct investment (FDI) in GDP; and (vi) human capital accumulation.
hdl:11540/4214
Keywords: O14; O47; O53; 330; balance of payments constrained growth rate; Kalman filter; natural growth rate; Okun's Law; People's Republic of China; potential growth rate; Zahlungsbilanz; Wirtschaftswachstum; Zustandsraummodell; Produktionspotenzial; Okunsches Gesetz; China